Impact of Domestic Violence on Children's Education in Colombia: Methodological Challenges. (October 2017) - Assaad, Ragui; Friedemann-Sánchez, Greta; Levison, Deborah
We explore the methodological challenges of estimating the effects of intimate partner violence (IPV) against the mother on the educational outcomes of her children. We tackle the problem of potential endogeneity and non-random selection of children into situations where they are exposed to IPV using non-parametric matching methods and parametric instrumental variable methods. Using Colombia's 2005 Demographic and Health Survey (DHS), we find that IV and non-IV estimators produce qualitatively similar results at varying degrees of precision, for some educational outcomes. Therefore, exogeneity of IPV to various education outcomes cannot be taken for granted; appropriate methods need to be used to study its causal effects.